Treating the field as a lab: A basic guide to conducting economics - Viceisza, Angelino C.G. (International Food Policy Research Institute, 2012)
Treating the Field as a Lab: A Basic Guide to Conducting Economics Experiments for Policymaking offers economists, researchers, and policymakers 19 basic principles for conducting experiments in developing-country contexts. In this Food Security in Practice technical guide, Angelino Viceisza focuses on the class of economics experiments known as lablike field experiments and examines their basic rationale, the details involved in conducting them, and some of the applications of them in the literature. In addition, Viceisza discusses the role of game theory in conducting field experiments and considers some of the typical issues that can arise when drawing inferences and deriving policy implications from experimental work.